The Flexibility of Poland’s Labour Market in the Light of the Theory of Optimum Currency Areas - Kawalec, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Labour market flexibility is understood as the ability of the market to smoothly adapt to changing economic conditions. To function smoothly and be flexible, the labour market must be able to quickly respond to the demand for labour and changes taking place in the economy. In the context of the theory of optimum currency areas, labour market flexibility plays a greater role as a substitute for flexibility of exchange rates in reducing shocks to the monetary union. The aim of this work is to analyse the current level of labour market flexibility in Poland, in particular in the context of the optimum currency area theory criteria. The most important conclusion from the analysis is that Poland’s labour market is too inflexible, and is therefore an effective alternative to exchange rate flexibility in macroeconomic adjustments.